2018
DOI: 10.1002/pad.1821
|View full text |Cite
|
Sign up to set email alerts
|

Network structure and collaborative innovation processes—A comparative analysis of two elderly service networks in Shanghai

Abstract: Summary How does the structure of government‐funded service networks affect the process of service innovation? We have conducted a comparative analysis of the structure and processes of collaborative innovation of 2 government‐funded community‐based elderly service networks in Shanghai. We have found that in consistent with the literature, a network that has a network administrative organization structure is better able to manage the process of service innovation in a way that balances the need to achieve gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
9
0
2
Order By: Relevance
“…The study provides evidence of how the new mode of party leadership and state regulation (through state-sponsored IOs) affected SOs' managerial strategies. Consistent with previous ones, the study concludes that Xi Jinping government has permitted space for SOs' development and facilitated SOs' participation in service design and policy development (Hsu & Hasmath, 2014;Lam & Li, 2018;Li & Yang, 2020). The noncoercive mode of state-society interaction found in this study questions the assumption that one party-state is "authoritarian," namely coercive, in all of its action toward societal actors.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…The study provides evidence of how the new mode of party leadership and state regulation (through state-sponsored IOs) affected SOs' managerial strategies. Consistent with previous ones, the study concludes that Xi Jinping government has permitted space for SOs' development and facilitated SOs' participation in service design and policy development (Hsu & Hasmath, 2014;Lam & Li, 2018;Li & Yang, 2020). The noncoercive mode of state-society interaction found in this study questions the assumption that one party-state is "authoritarian," namely coercive, in all of its action toward societal actors.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…Although these research findings are contrary to the mainstream international PPP literature, there is some recent evidence that supports this article's line of argument. In their comparative analysis of two elderly service networks in Shanghai, Lam and Li (2018) found that despite the dominant role of lead organisation and centralised processes, a network was able to attain a high level of competence by delivering high quality services. It is interesting to note that this piece of evidence is from China that characterises authoritarian political system which is very different to the Western civilisations, hence reiterating the significance of context.…”
Section: Discussionmentioning
confidence: 99%
“…Although these research findings are contrary to the mainstream international PPP literature, there is some recent evidence that supports this article's line of argument. In their comparative analysis of two elderly service networks in Shanghai, Lam and Li (2018) found that despite the dominant role of lead organisation and centralised processes, a network was able to attain a high level of competence by delivering high quality services.…”
Section: Level Of Coproductionmentioning
confidence: 99%
“…Pesquisas sugerem que a inovação pública de "baixo para cima", que envolve os cidadãos na coprodução de serviços públicos, muitas vezes ajuda a superar os problemas causados pelo financiamento limitado do governo, em especial por meio da identificação efetiva de problemas sociais e das necessidades dos usuários de serviços, do desenvolvimento de confiança entre os cidadãos e da redução de custos para os contribuintes (Lam & Li, 2018).…”
Section: Inovação Colaborativa E Liderança No Setor Públicounclassified